Socio–Economic Factors and Health Status as Determinants of Public Service Retirees’ Life–Satisfaction in the South–West, Nigeria (2015)
Public service retirees in South-West Nigeria face quite a number of challenges which affect their life satisfaction and overall well being; most often with resultant shortened life span few years after retirement. Previous studies have focused more on pension and other benefits as well as problems related with ageism without adequate consideration for the combined effects of socio-economic factors (accommodation, dependent children, family type, other dependents, community commitment and participation, family size, taste and fashion, pension, gratuity, additional source of income, post retirement employment) and health status on the public service retirees’ life satisfaction. This study, therefore, investigated the socio economic factors and the health status as determinants of life satisfaction among public service retirees in South-West, Nigeria. The survey design of ex-post facto was adopted. All the six states of the South-West, Nigeria which include Ekiti, Lagos, Ogun, Ondo, Osun and Oyo were enumerated. One thousand eight hundred members of the Nigerian Union of Pensioners who were disaggregated to three hundred participants in each of the state were randomly selected for the study. Dieners’ Satisfaction with Life scale (r=0.92); Leung and Earl’s Health Status scale (r=0.85), Social Factor Questionnaire with (seven sub segments) Accommodation (r=0.23); Dependent Children (r=0.20); Family type (r=0.15); Other Dependants (r=0.46); Community Commitment and Participation (r=0.28); Family size (r=0.27); Taste and Fashion (r=0.38) scales; and Economic Factor Questionnaire with (five sub segments) Pension (r=0.16); Gratuity (r=0.48); Additional source of Income (r=0.32);Post Retirement Employment (r=0.45); and Size and Level of Investment (r=0.39) scales were used for data collection. These were complemented with six sessions of focus group discussion with selected retirees; one session per state. Three research questions were answered and four hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson product moment correlation, Analysis of Variance, multiple regression and content analysis. Participants were 1,111 males and 684 females with mean age of 60.3 years. Socio-economic factors jointly influenced public service retirees’ life satisfaction (F (13.1772) = 45.97). Family size (β=0.22), taste and fashion (β=0.20), pension (β=0.20), family type (β=0.16) gratuity (β=0.14), dependent children (β=0.11), community commitment and participation (β=0.99), accommodation (β=0.10), additional source of income (β=0.12), size and level of investment (β=0.63), had relative contributions to public service retirees life satisfaction, while post retirement employment and other dependants did not. There was no significant difference in the life satisfaction based on gender of public service retirees. However, there was a difference in life satisfaction based on marital status; in which married (x̄ = 16.02) and divorced (x̄ = 15.40) were more satisfied with life than widowed (x̄ = 15.07), (F (2, 1797) = 3.33).The features of life satisfaction among public service retirees are; good relationship with family members (70.0%), participation in community activities (68.0%) and membership of social clubs (60.0%). Socio-economic factors and health status have been found to positively influence public retirees’ life satisfaction. Therefore, retirement benefits should be paid promptly, while other essential needs of the retirees should be provided under a functional social security system.